Biomass and wind energy as sources of renewable energy for a more sustainable environment in Indonesia: a review - Erdiwansyah, E.; Gani, Asri; Rizalman, Mamat; Mahidin, M.; Sudhakar, Kumarasamy; S. M., Rosdi; Husin, Husni (Polish Academy of Sciences, 2022)
Pollution continues to experience a rapid increase so cities in the world have required the use of renewable energy. One of the keys that can prevent climate change with a sustainable system is renewable energy. Renewable energy production, especially for hybrid systems from biomass and wind, is the objective of the analysis in this work. The potential of feedstock for different biofuels such as bio-diesel, bio-ethanol, bio-methane, bio-hydrogen, and biomass is also discussed in this paper. The sustainability of the energy system for the long term is the main focus of work in this investigation. The configuration of the hybrid system between biomass energy and wind energy as well as some problems from various design factors are also presented. Based on the findings, this alternative energy utilization through biomass-based hybrids can save costs and improve environmental conditions, especially for the electrification of off-grid rural areas. This paper will provide important information to policymakers, academics, and investors, especially in carrying out the development and factors related to the utilization of wind-biomass-based hybrid energy systems.